PENGARUH PARTISIPASI MASYARAKAT TERHADAP KEBERLANJUTAN KONSERVASI LINGKUNGAN DI DESA TARUB TEGAL - Nur Hamid Hamid (Fakultas Dakwah dan Ilmu Komunikasi, 2023)
The Women Farmers Group (KWT) is a forum for the community, especially women, to manage and express various ideas in agriculture, as well as a forum for group members to increase knowledge and insight. The purpose of this study is to analyze the effect of community participation on the sustainability of environmental conservation. This type of research is quantitative research the population used in this study was 210. sample selection used simple random sampling and the sample size was 67 respondents. The results of this study are that community participation affects the sustainability of environmental conservation. This can be seen in the results of the simple linear regression test with the results of the variable X regression coefficient value of 0.821 with a significance value of 0.000 0.05 with an R Square value of 0, 646 or as much as 64.6% of the contribution given by community participation to the sustainability of environmental conservation.